Nonlinear ACD model and informed trading: Evidence from Shanghai Stock Exchange - Woon K. Wong; Dijun Tan; Yixiang Tian (Cardiff University, Cardiff Business School, 2008)
Dufour and Engle (J. Finance (2000) 2467) find evidence of an increased presence of informed traders when the NYSE markets are most active. No such evidence, however, can be found by Manganelli (J. Financial Markets (2005) 377) for the infrequently traded stocks. In this paper, we fit a nonlinear log-ACD model to stocks listed on Shanghai Stock Exchange. When trading volume is high, empirical findings suggest presence of informed trading in both liquid and illiquid stocks. When volume is low, market activity is likely due to liquidity trading. Finally, for the actively traded stocks, our results support the price formation model of Foster and Viswanathan (Rev. Financial Studies (1990) 593).
Keywords: G11; G14; G15; 330; Informed trading; Liquidity trading; Duration; Volume; Volatility; Wertpapierhandel; Börsenmakler; Information; Börsenumsatz; Volatilität; USA; New York (NY)